2018
DOI: 10.1136/bmjsem-2018-000422
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial remodelling and tissue characterisation by cardiovascular magnetic resonance (CMR) in endurance athletes

Abstract: There is still some controversy about the benignity of structural changes observed in athlete’s heart, especially regarding the observation of increased biomarkers and the presence of myocardial fibrosis (MF).AimOur purpose was to evaluate by cardiovascular magnetic resonance (CMR) the presence of diffuse as well as focal MF in a series of high-performance veteran endurance athletes.MethodsThirty-four veteran healthy male endurance athletes, still being in regular training, with more than 10 years of training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…typically > 35 yrs). We found a harmonious dilatation of the 2 ventricles, and a moderate increase in total ventricular mass, in accordance with previous description of athlete's heart syndrome in master athletes [17] . Values for these parameters did not exceed the pathological thresholds hypertrophic cardiomyopathy [29] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…typically > 35 yrs). We found a harmonious dilatation of the 2 ventricles, and a moderate increase in total ventricular mass, in accordance with previous description of athlete's heart syndrome in master athletes [17] . Values for these parameters did not exceed the pathological thresholds hypertrophic cardiomyopathy [29] .…”
Section: Discussionsupporting
confidence: 93%
“…However, it is under debate whether the cumulative effects of intensive endurance exercise induce chronic cardiac damage [3] , [4] , [5] , especially in master athletes. It has been proposed that long-term endurance exercise may be associated with myocardial fibrosis (MF) detected by late gadolinium-enhancement (LGE) cardiac magnetic resonance (CMR) [6] , [7] , [8] , [9] , [10] , [11] , and/or with right ventricle contractile dysfunction [12] , creating a potential substrate for ventricular arrhythmia [13] , but these aspects are not constantly found across studies [14] , [15] , [16] , [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
“…This can help in the differential diagnosis in this group of patients if deemed necessary [5,7]. Finally, presented observations may help to explain the paradox between cardiac troponin increase after the endurance physical activity and lack of permanent myocardial injury in life-long elite runners observed in other studies [4,6,7,[13][14][15]. As the increase in troponin concentration even after an extremely long race is very mild is it unlikely that it can lead to significant myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 80%
“…Troponin rise after exercise is 2 of 9 usually discrete with levels returning to reference values within hours [8] and may be accompanied by an increase of natriuretic peptide levels and transient decrease of left or right ventricular systolic function without long-term consequences [9][10][11][12]. In line with that, recent studies with new imaging techniques demonstrated that intensive endurance training does not seem to promote myocardial fibrosis [6,[13][14][15].…”
Section: Introductionmentioning
confidence: 82%
“…In a study of 50 patients with HCM, 40 athletes, and 35 sedentary volunteers, the T1 values and ECV of the thickest segment in athletes were lower than HCM [ 86 ]. Most of the studies showed there were no significant differences in terms of T1 mapping and ECV between athletes and controls [ 87 , 88 ].…”
Section: Non-ischemic Cardiomyopathymentioning
confidence: 99%